2018
DOI: 10.1364/boe.9.004552
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in infrared laser lithotripsy [Invited]

Abstract: The flashlamp-pumped, solid-state, pulsed, mid-infrared, holmium:YAG laser (λ = 2120 nm) has been the clinical gold standard laser for lithotripsy for over the past two decades. However, while the holmium laser is the dominant laser technology in ureteroscopy because it efficiently ablates all urinary stone types, this mature laser technology has several fundamental limitations. Alternative, mid-IR laser technologies, including a thulium fiber laser (λ = 1908 and 1940 nm), a thulium:YAG laser (λ = 2010 nm), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 121 publications
(63 citation statements)
references
References 110 publications
0
63
0
Order By: Relevance
“…The CO 2 laser had a 137.5 W peak power that was 2.5 times higher than its 55 W average power, while the CO laser showed a 86 W peak power that was 1.4 times higher than its 60 W average power. Recent “superpulsed” Tm:fiber lasers achieve peak powers of 500 W, pulse rates of up to 2 kHz, and pulse lengths of 200 microseconds to 12 milliseconds [30]. “Ultrapulsed” CO 2 lasers that are used for fractional ablation have peak powers of about 240 W, 2 MHz repetition frequency, and pulse lengths of 90 microseconds to 2 milliseconds.…”
Section: Discussionmentioning
confidence: 99%
“…The CO 2 laser had a 137.5 W peak power that was 2.5 times higher than its 55 W average power, while the CO laser showed a 86 W peak power that was 1.4 times higher than its 60 W average power. Recent “superpulsed” Tm:fiber lasers achieve peak powers of 500 W, pulse rates of up to 2 kHz, and pulse lengths of 200 microseconds to 12 milliseconds [30]. “Ultrapulsed” CO 2 lasers that are used for fractional ablation have peak powers of about 240 W, 2 MHz repetition frequency, and pulse lengths of 90 microseconds to 2 milliseconds.…”
Section: Discussionmentioning
confidence: 99%
“…It is, therefore, also postulated that water present in intercrystalline spaces, pores, cracks, and fissures of human kidney stones undergo thermal expansion and vaporization during laser lithotripsy, thus contributing to the fragmentation of stones [35]. The thermal expansion coefficient of water is an order of magnitude higher than that for kidney stones with high pressure due to water vaporization contributing to this mechanism [36]. Recent scanning electron microscopy studies also show evidence of crack formation in kidney stones and partly unaltered crystalline composition of stone dust after laser lithotripsy, providing further evidence supporting this mechanism [4,37].…”
Section: Water Absorption Peakmentioning
confidence: 99%
“…The experimental Thulium fiber laser (TFL) is currently being studied as a potential alternative to the Holmium laser for treatment of kidney stones. Potential advantages of TFL technology have recently been reviewed in the literature [19,20]. While the majority of previous reports have been based on preliminary laboratory studies [21][22][23][24][25], the TFL has also shown promise in early clinical studies as well [26][27][28].…”
Section: Thulium Fiber Laser Lithotripsymentioning
confidence: 99%